Analysis of Project Acceleration with Crashing Method on the Rehability and Renovation Project Work of Iain Ambon Library - Nukuhaly, Ismit; Serang, Rudi (International Journal of Advanced Engineering Research and Science, 2022)
The construction of a construction project often happens something that is not desirable such as the occurrence of delays in work on the project. Many factors cause delays, one way to anticipate it is by accelerating. In accelerating, the cost and quality factors must be considered, so that the optimum cost and quality are obtained according to the desired standard. The construction of the Iain Ambon Library Rehabilitation and Renovation Project was chosen for a research study due to delays in its implementation. The Critical Path Method can be used to schedule project execution time with the consideration that this method is more effective and efficient. The optimization of time and cost is obtained from the Crash Program with the Network Planning system with the Crashing method by adding accelerated working hours for each job. The acceleration is carried out on the work on the critical path with the lowest cost slope. The results of the analysis show that the total project budget under normal conditions is IDR 1,456,082,119 with a duration of 70 days, in the post-crashing condition with the alternative of adding two hours of working hours, it is IDR 2,246,877,528 or more expensive than the total project cost budget under normal conditions. and the duration of the project implementation is 51 working days or faster than the normal duration